Компаративні методи дослідження графічної знакової символіки трипільської культури - Годенко-Наконечна, О. (Студії мистецтвознавчі, 2008)
Quintessential of Eneolithic art of Thrypillya-Kukuteni culture is ceramics, especially ceramic painting and graphic exactly, which is system of graphical signs and symbols. The retrospective method which contains comparative-typological one is the traditional in Thrypillya signs and symbols studies.